Elevated Interleukin‐17A expression in amlodipine‐induced gingival overgrowth. (16th March 2020) - Sume, Siddika Selva; Berker, Ezel; Ilarslan, Yagmur; Ozer Yucel, Ozlem; Tan, Cagman; Goyushov, Samir; Gultekin, Sibel E.; Tezcan, Ilhan
Abstract : Background and objectives: Amlodipine, a calcium channel blocker derivative, is frequently used by patients with high blood pressure. Studies reported that it can induce gingival overgrowth. However, the underlying mechanism is not fully described yet. Interleukin‐17A (IL‐17A) is known as a proinflammatory cytokine, but current studies indicate that it has a role in fibrotic disorders and epithelial‐mesenchymal transition (EMT). The aim of this study was to figure out the possible role of IL‐17A in amlodipine‐induced gingival overgrowth. Materials and methods: Twenty‐nine (29) individuals participated in the study, and they were assigned into 3 groups based on medical status and clinical periodontal examination; 9 patients with amlodipine‐induced gingival overgrowth, 11 patients with inflammatory gingival overgrowth, and 9 healthy individuals as a control group. Clinical periodontal parameters including plaque index (PI), gingival index (GI), and gingival overgrowth index (GOI) were recorded. Blood and gingival crevicular fluid (GCF) samples were obtained. Gingival tissues were taken by appropriate periodontal surgery following initial periodontal therapy. To detect IL‐17A on tissue samples, immunohistochemistry (IHC) was performed. Quantitative analysis was done, and the expression level of IL‐17A was given as the percent positively stained cells. Enzyme‐linked immunosorbent assay (ELISA) kits were used to analyze IL‐17A in serum and GCF samples. Results: All recorded clinical parameters were significantly higher in gingival overgrowth groups compared with control. Evaluation of inflammation on tissue sections did not show any significant change within the groups. Immunohistochemistry findings showed that IL‐17A expression was increased in amlodipine samples (81.90%) compared with control samples (42.35%) ( P < .001). There was an increase in the inflammatory group (66.08%) which is significantly less than the amlodipine group ( P < .05). IL‐17A levels in serum and GCF samples were not different within the study groups. Conclusion: In this study, elevated IL‐17A expression regardless of inflammation shows that amlodipine might cause an increase of IL‐17A in gingival tissues. This increase might induce fibrotic changes and EMT in gingival overgrowth tissues. The association of IL‐17A with fibrosis and EMT in gingival tissues requires further investigation.